On the Distance between Three Arbitrary Points - Parin Chaipunya; Poom Kumam (Journal of Function Spaces and Applications)
We point out some equivalence between the results in (Sedghi et al., 2012) and (Khamsi, 2010). Then, we introduce the notion of a general distance between three arbitrary points and study some of its properties. In the final section, some fixed point results are proposed.